Batak Toba’s Diaspor Loyalty against Customary Heritage in Special Region of Yogyakarta - Dhuwik Afriliani; Setiati Widihastuti (Yogyakarta State University, 2022)
Various problems due to meetings between two or more cultures such as shock culture, cultural assimilation, and cross culture are considered to be problems of the diaspor community until now. The question is, is this problem also experienced by the Batak Toba’s diaspor, which incidentally is considered a tribe that is very loyal to the customs of their ancestral heritage? Then, how their efforts to maintain the sustainability of traditional marriages? To answer this question, a study was conducted on 8 (eight) Batak Toba’s diaspor in Special Region of Yogyakarta (DIY). The main findings in the study raised from descriptive research with a qualitative approach include: love of the Batak’s custom and the existence of social sanctions encourage the Batak Toba’s diaspor to hold tight to the tradition up to now, it encourages them to try to instill customary valuesand principles, provide direct practical learning to naposo, held traditional seminars, persuaded to directly deal with each marriage, and actively involved in their respective pockets so that their traditional marriages would be preserved. However, in this effort there are still some obstacles, one of which is the indifference of naposo in the management of the HKBP Church. This study recommends the need to allocate a portion of HKBP Church funds to provide guidance by providing free housing for naposo who migrate to DIY.